Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Belajar Peserta Didik - M. Asep Fathur Rozi; Nabilah, Miftah Marwa (DIMAR: Jurnal Pendidikan Islam, 2023)
This research is motivated by looking at the existing reality, the learning process of Islamic Religious education such as Al-Qur'an Hadith, Aqidah Akhlak, Fiqh, and Islamic Cultural History in class seen as less effective and less creative in using various methods and media during the teaching and learning process takes place. So that some students are less enthusiastic and tend not to pay attention to the teacher's explanation, and are even busy with their respective activities. The focus of this research is the role of PAI teachers in improving the quality of student learning, the supporting and inhibiting factors for PAI teachers in improving the quality of student learning, and the efforts made by PAI teachers in improving the quality of student learning. This research uses a descriptive qualitative type at Muhammadiyah Islamic Junior High School Bandung Muhammadiyah Boarding School (MBS 1) Tulungagung. Data was taken from the head of the madrasa, the deputy head of curriculum, and PAI teachers. Collecting data process using observation, interviews, and documentation. The results of this study are the role of PAI teachers in improving the quality of student learning as educators, guides, facilitators, and motivators. Supporting factors are professional PAI teachers and the availability of adequate facilities and infrastructure. Inhibiting factor lies in the differences in characteristics that exist in students. PAI teachers' efforts to improve the quality of student learning by teaching material using interesting methods accompanied by motivation.